Becoming multi-lingual in Hong Kong: The dilemmas of South Asian Students. (18th October 2018) - Tsung, Linda; Lau, Eva
Abstract : This study examined Chinese language learning among South Asian students in Hong Kong. The mixed methods research design included two separate studies. Study 1 was a quantitative study in which a survey was administered to 387 South Asian students to examine their self-perceived language proficiency in Chinese, their mother tongue, and English. Study 2 was a qualitative study in which individual interviews were conducted with 25 South Asian students to identify the factors that influenced their Chinese language learning. The results showed that South Asian students have low self-perceived Chinese proficiency. In particular, students reported difficulty in mastering reading and writing skills in Chinese. Findings also indicated that teachers' skills, family support, and both instrumental and integrative motivational orientations influenced South Asian students' Chinese language learning. The implications of the present study for promoting ethnic minority students' language learning in both local and other multicultural contexts are discussed, as are the limitations of the study and directions for future research.